Assessing Quality of Life After Orthognathic Surgery in Disabled Patients. Issue 8 (November 2019) - Promerat, Alexandra; Touzet-Roumazeille, Sandrine; Schlund, Matthias; Ferri, Joel
Abstract : Introduction: Orthognathic surgery is a common procedure in facial deformities treatment but requires a high level of compliance from the patient. Performing this treatment for mentally disabled patients is a subject of discussion. The aim of this study was to evaluate the quality of life (QOL) after orthognathic surgery in disabled patients. Material and methods: Eight patients with mental disability who underwent orthognathic surgery between 2007 and 2017 participated in this study. Their family or guardian completed a questionnaire to assess modification in aesthetic, functional, and social abilities after orthognathic surgery. Complications, difficulties in maintaining postoperative cares were also recorded. Results: All patients had improvement in global facial aesthetic. 62.5% of the patients had improvement in self-esteem and confidence in social events. Regarding functional aspect, the main improvement was found in chewing (75%) and ability to move the jaw (75%). Two patients (25%) found that jaw noises and pain were worse after surgery. No major complication occurred. Postoperative care was hard to follow but no patient had to stop maxillomandibular fixation. Conclusion: On well selected cases, orthognathic surgery is a safe procedure which provides improvement in QOL in disabled patients. Abstract : Supplemental Digital Content is available in the text